APLIKASI BIOCHAR, KOMPOS DAN UREA TERHADAP BEBERAPA SIFAT FISIKA TANAH, PERTUMBUHAN, DAN HASIL TANAMAN KAYLAN (Brassica oleraceae) - Muhammad, Darusman, Chairunnas (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2015)
Abstract: Soil physical properties consist of bulk density, total porosity, permeability, stability indices, and pore distribution were affected by aplication of biochard, compost and urea. This study aimed to determine the influence of some physical properties of soil, growth and yield Kaylan affected by the application of biochard, compost and urea. Research using randomized block design (RAK), consisting of three factors, namely biochar, compost and urea. Applications biochar, compost and urea as the sole factor significantly influeced soil bulk density, soil porosity, permeability, index stability of aggregated soil, drainage pore of rapid soil, drainage pore of slow soil, pore water available soil, plant height after 7, 14, 21 and 28 days planting (DAP), number of leaves a 14, 21, and 28 days after planting, and the wet weight of Stover plants. Interaction application of biochar, compost and urea significantly affected bulk density, stability index aggregated soil, plant height DAP aged 14 and 28, as well as the number of plant leaves Kaylan ages 21 and 28 DAP.Kata kunci : Biochar, Kompos, urea, Sifat fisika Tanah